Effect of Room Temperature on Humidity and Water Content of Volcanic Soil - Ingrid Sisilia Garedja; Andrias Suhendra Nugraha (Universitas Medan Area, 2026)
Volcanic soil is characterized by high porosity and excellent water retention capacity, making its moisture characteristics highly sensitive to environmental conditions. This study aims to evaluate the effect of room temperature on the humidity and water content of volcanic soil and to examine the relationship between these parameters during laboratory storage. An experimental study was conducted using volcanic soil collected from Lagadar, West Bandung Regency, West Java, Indonesia. Relative humidity and room temperature were measured using an AS847 humidity meter, while water content was determined in accordance with ASTM D2216. The observations were performed over a 28-day period under uncontrolled laboratory environmental conditions. The results showed that relative humidity gradually decreased over time due to the natural drying process of the soil samples. An increase in room temperature was associated with reductions in both relative humidity and water content, indicating that evaporation played a significant role in moisture loss. Furthermore, relative humidity exhibited a strong positive correlation with water content, suggesting that humidity measurements can be used as an indicator of moisture changes in volcanic soils. These findings improve the understanding of the influence of environmental conditions on the moisture behavior of volcanic soils and provide useful information for laboratory material storage and future geotechnical applications.